Description of Student Learning Motivation to Online Practices - Yuliar Maulana; Wastu Adi Mulyono; Anas Sumeru (Journal of Bionursing, 2021)
Background: The pandemic makes online learning methods the right choice so that the learning process can continue. The learning methods in universities generally consist of the lecture/lecturer method and the skill lab method. The online practicum method is packaged in audio-visual form but has the disadvantage that the opportunity for red-demonstration cannot be carried out optimally due to limited tools and materials as well as supporting facilities. This is one of the factors that can affect student learning motivation to decrease. Methods: This study used a retrospective descriptive research design. The population to be studied is the students of the Department of Nursing at Jenderal Soedirman University using the Stratified Random Sampling technique and obtained 183 respondents. This study uses a questionnaire regarding the ARCS-V Motivation model (Keller 2016) which has been modified. Data analysis to be carried out is univariate analysis. Results: The results of the study that students' learning motivation towards online learning was included in the low category, quite a lot, namely there were 27 students (14.75%). 133 students (72.68%) with moderate learning motivation and 23 students (12.57%) with high learning motivation. Conclusion: The results showed that students' learning motivation towards online learning was included in the medium-high category range. This shows that online practicum can increase learning motivation. Online practicum is a solution for practical learning methods in the COVID-19 pandemic situation.